Pipersentan: A De Novo Synthetic Endothelin Receptor Antagonist that Inhibits Monocrotaline- and Hypoxia-Induced Pulmonary Hypertension - Zhang, Zeyu; Liu, Chunlei; Bai, Yongyi; Li, Xin; Gao, Xiaojian; Li, Chen; Guo, Ge; Chen, Si; Sun, Mingzhuang; Liu, Kang; Li, Yang; He, Kunlun (Frontiers in Pharmacology, 2022)
Background: Although major advances have been made in the pathogenesis and management of pulmonary arterial hypertension (PAH), the endothelin system is still considered to play a vital role in the pathology of PAH due to its vasoconstrictive action. Endothelin receptor antagonists (ERAs), either as monotherapy or in combination with other drugs, have attracted much attention in the treatment of this lethal disease, and research is continuing. Methods: A novel ERA, pipersentan 5-(1,3-Benzodioxol-5-yl)-6-[2-(5-bromopyrimidin-2-yl)oxyethoxy]-N-(2-methoxyethylsulfamoyl)pyrimidin-4-amine, was recently synthesized and the physicochemical characterizations and the pharmacology both in vitro and in vivo were studied. Results:This orally administered ERA can both competitively and selectively inhibit the binding of endothelin-1 (ET-1) to its receptors with good physicochemical characteristics. Pipersentan efficaciously antagonized the effects of ET-1 on pulmonary artery smooth muscle cell proliferation, migration and calcium mobilization and effectively improved right ventricular hypertrophy and pulmonary arterial pressure in both monocrotaline- and hypoxia-induced pulmonary hypertension (PH) rat models. Conclusions: This profile identifies pipersentan as a new agent for treating ET-1 system activation-related PH.